Isolation and assessment of potential probiotic microorganisms from modified indigenous foods preparation - Verma, Smrati; Sigh Chaudhary, Hotam; Singh, Balwant; Gopalan, N; Singh, Anil kumar (Pharmacognosy Communications)
Objective: The objective of present study is to isolate potential probiotic microorganisms from modified indigenous foods and assessment of its antimicrobial activity against some selected pathogenic strains including E. coli, E. faecilis, K. pneumonia, S. dysentrae, S.epidermidis, S. saprophyticus, S. pyogenes and S. aureus. These isolated microorganisms were further characterized using microscopic and biochemical methods. Method: Six different set of probiotic indigenous foods were prepared by Bulgur Wheat and Corn grits. Each probiotic isolate was grown in Man Rogasa Sharp (MRS) broth for 24 h at 37°C in order to prepare Cell Free Supernatant (CFS) The CFS obtained from isolated strain was tested for antimicrobial activity by well diffusion method. Results: The study finally led us to isolate creamy white, circular, convex elevated and smooth rough textured colonies by using MRS agar containing bromocresol purple. The isolates were Gram positive, rod shaped, catalase negative and shows increase in antimicrobial activity (zone of inhibition) of isolates CFS against E.coli (22.3±1.2), E. faecalis (23±0.8), S. pyogenes (24.3±0.4), S. saprophyticus (18 ± 0.8), S. aureus (16.6±0.4), S.epidermidis (17±0), K. pneumonae (18±0.8), S. dysentrae (17±0.8), which is more than processed probiotic CFS. It was observed that isolates demonstrated good capacity to resist bile salts by showing growth under exposure to 0.3% bile salts and able to grow in pH 2 as well as pH 3. Conclusion: These results suggest that these isolates could successfully transit the human stomach and may be capable of reaching the intestinal environment and functioning effectively there.
Keywords: Probiotics; Antimicrobial activity; Pathogenic microorganisms; Probiotic foods